State of the Art of Pathologic and Molecular Testing - Dacic, Sanja (Hematology/oncology clinics of North America, 2023)
Advances in the treatment of non-small cell lung carcinoma have resulted in improved histologic classification and the implementation of molecular testing for predictive biomarkers into the routine diagnostic workflow. Over the past decade, molecular testing has evolved from single-gene assays to high-thoroughput comprehensive next-generation sequencing. Economic barriers, suboptimal turnaround time to obtain the results, and limited tissue available for molecular assays resulted in adoption of liquid biopsies (ctDNA) into clinical practice. Multiplex immunohistochemical/immunofluorescence assays evaluating tumor microenvironment together with the AI approaches are anticipated to translate from research into clinical care.